Stress and recovery of New Zealand junior rowers preparing for the 2008 World Championships: Comparison to the 1998 German national team - Nottle, C.; van Warmerdam, M. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Manipulation of training load is a key stimulus for improved performance, however overtraining can result in performance declines and burnout. Previously Kellmann et al [1] examined the stress, recovery and training duration of the German (GER) Junior Rowing Team preparing for the 1998 World Championships. The aim of the current investigation was to compare these results with the stress, recovery and training duration of the New Zealand (NZL) Junior Rowing Team preparing for the 2008 World Championships. Methods Athletes from the New Zealand Junior National Rowing Team volunteer for the study (N=24, mean±SD age: 17.4±0.5 years, height: 181.3±9.5 cm, weight: 81.3±10.1 kg, ?8 skinfolds: 73.1±20.9). Athletes were monitored for 5 weeks of a training camp held immediately prior to the 2008 World Junior Championships. Athletes completed five Recovery-Stress Questionnaires for Athletes (RESTQ-Sport) and a daily training diary outlining mode, duration and intensity of training. Descriptive data (mean±SD) for each scale of the RESTQ-Sport and training duration was determined for each week. These data were compared with data presented for the German athletes via determination of z- or t-scores. Results No differences in training duration between the two groups was recorded (t=0.5) with average weekly durations of 1090 and 1109 hours reported for the NZL and GER athletes respectively. For the stress scales: NZL athletes reported significantly higher scores for emotional stress (z=5.6), social stress (z=3.16), conflicts/pressure (z=3.9), fatigue (z=4.9), lack of energy (z=12.5) and physical complaints (z=7.8). For the recovery scales: NZL athletes reported significantly lower social recovery (z=-11.6), physical recovery (z=-4.6), general well being (z=-4.8) and sleep quality (z=-10.0). For the sport specific scales: NZL athletes reported significantly higher scores for disturbed breaks (z=8.6), emotional exhaustion (z=12.0), and injury (z=10.1) and significantly lower scores for being in shape (z=-3.6) and self efficacy (z=-2.6). At their respective events the GER athletes placed in 14/14 A finals (14 crews), with the NZL athletes placing in 3/3 A finals (5 crews). Conclusions While comparisons indicated no differences in training duration, the NZL athletes demonstrated higher stress and less recovery compared to the GER athletes. It is possible this is the result of differences in training intensity not duration, which is demonstrated to be related to overtraining (Halson et al. [2]). Although it is difficult to compare the performance outcomes of the teams, the long term consequences of high stress: low recovery for the NZL athletes may be a concern with regards to athlete development, and progression to seniors, due to the relationship between stress- recovery and burnout.